BV Solutions of Dirichlet Problem for a Class of Doubly Nonlinear Degenerate Parabolic Equations (Journal of Partial Differential Equations, 2004)
The uniqueness and existence of BV solutions to Dirichlet problem of doubly degenerate parabolic equations of the following form \frac{∂u}{∂t} = div(A(|∇B(u)|)∇B(u)) in Q_T = Ω × (0, T) are studied.
Keywords: Doubly degenerate equations; Dirichet problem; BV solution